2013
DOI: 10.1159/000355295
|View full text |Cite
|
Sign up to set email alerts
|

Response Inhibition in Pedophilia: An fMRI Pilot Study

Abstract: Background: The failure to inhibit pleasurable but inappropriate urges is associated with frontal lobe pathology and has been suggested as a possible cause of pedophilic behavior. However, imaging and neuropsychological findings about frontal pathology in pedophilia are heterogeneous. In our study we therefore address inhibition behaviorally and by means of functional imaging, aiming to assess how inhibition in pedophilia is related to a differential recruitment of frontal brain areas. Method: Eleven pedophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…According to the finding that the VMPFC plays a critical role in inhibitory control [Bari and Robbins, ; Chikazoe, ] and, moreover, was reported to be altered in offending pedophiles [Kruger and Schiffer, ; Mendez and Shapira, ; Schiffer et al, ; Schiffer and Vonlaufen, ], we subsequently hypothesized that P + CSO as compared to both non‐offending groups would show different BOLD signal change during response inhibition in related medial prefrontal areas. Similarly, in P + CSO we expected aberrant BOLD activity in medial parietal regions [Habermeyer et al, ; Kärgel et al, ] when compared to P‐CSO and HC.…”
Section: Introductionmentioning
confidence: 79%
“…According to the finding that the VMPFC plays a critical role in inhibitory control [Bari and Robbins, ; Chikazoe, ] and, moreover, was reported to be altered in offending pedophiles [Kruger and Schiffer, ; Mendez and Shapira, ; Schiffer et al, ; Schiffer and Vonlaufen, ], we subsequently hypothesized that P + CSO as compared to both non‐offending groups would show different BOLD signal change during response inhibition in related medial prefrontal areas. Similarly, in P + CSO we expected aberrant BOLD activity in medial parietal regions [Habermeyer et al, ; Kärgel et al, ] when compared to P‐CSO and HC.…”
Section: Introductionmentioning
confidence: 79%
“…In 2013, by fMRI, researchers found that pedophiles had altered activities, especially in frontal areas (Wiebking, C. at al, 2013). In 2013 in an fMRI pilot study researchers concluded that, "Slower reaction time and less accurate visual target discrimination in pedophilia, was accompanied by attenuated deactivation of brain areas, belonging to the default mode network" (Habermeyer, B. at al., 2013). In 2015 researchers published detailed study on pedophiles and emphasized that through sMRI, fMRI have found REVIEW ARTICLE tools that can give us the possibility of confronting the data in 3D.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, functional neuroimaging has been able to support neither the association of paedophilic behaviour with frontal lobe disorder [22], nor the hypothesis that paedophilic individuals show deficits in cognitive or perceptual categorization of sexual stimuli [21].…”
Section: Key Pointsmentioning
confidence: 95%